NIAW 4028 (Phule Anurag): A new blast resistant bread wheat variety for restricted irrigation conditions of Peninsular India - Magar, Nilesh Madhavaro; Dodake, Suresh; Gadekar, Dnyandeo; Game, Bhanudas; Patil, Yogesh; Mhaske, Bhalchandra; Malunjkar, Bharat; Chitodkar, Sanjay; Lokhande, Rajendra (Journal of Cereal Research, 2024)
A new bread wheat variety NIAW 4028 (Phule Anurag) (IC No 650322) has been developed by Agricultural Research Station, MPKV, Niphad. It was identified and recommended by Varietal Identification Committee Meeting held in 62nd AGM of All India Coordinated Research Project on Wheat & Barley at MPUAT, Udaipur during August 2023. When tested in AICRP trials, it recorded a potential yield of 46.80 q ha-1 under restricted irrigation and showed stable performance across the zone by appearing 15 out of 24 times in the statistically superior group. Additionally, it showed resistance to wheat blast and both stem and leaf rust. The variety was released and notified by the Central Sub-Committee on Crop standards, Notification, and Release of Varieties in India vide notification number S.O.1560 (E), dated 26th of March, 2024 for cultivation in Peninsular Zone of India comprising states of Maharashtra, Karnataka, Telangana & Andhra Pradesh and Tamil Nadu (except Nilgiris & Palani Hills).